2006
DOI: 10.1159/000089952
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Matrix Metalloproteinases 2, 7 and 9, and Their Tissue Inhibitors 1 and 2, in Developing Rabbit Tracheae

Abstract: Background: Structural changes in the developing conducting airway impact the rigidity of the airway, altering the airway’s ability to sustain its shape during ventilation. The developmental changes in airway compliance oppose the changes in compliance of the developing lung; thus the expression profiles of matrix modeling proteins likely are also opposite in these developing organs. Objectives: To determine the profiles of matrix metalloproteinases (MMPs) -2, -7, and -9 and tissue inhibitors (TIMPs) -1 and -2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Loading buffer was added to ASF samples, and equal volumes of each sample were loaded into gels for electrophoresis. Protein was separated in 10% acrylamide gels containing 1 mg/mL gelatin (MMP-2 and MMP-9; Sigma Chemical Co., St. Louis, MO) or casein substrate (MMP-7; Sigma Chemical Co.) as previously described (24). After electrophoresis, SDS was eluted by washing the gels in 2.5% Triton-X-100.…”
Section: Methodsmentioning
confidence: 99%
“…Loading buffer was added to ASF samples, and equal volumes of each sample were loaded into gels for electrophoresis. Protein was separated in 10% acrylamide gels containing 1 mg/mL gelatin (MMP-2 and MMP-9; Sigma Chemical Co., St. Louis, MO) or casein substrate (MMP-7; Sigma Chemical Co.) as previously described (24). After electrophoresis, SDS was eluted by washing the gels in 2.5% Triton-X-100.…”
Section: Methodsmentioning
confidence: 99%
“…Substrate zymography and reverse zymography were performed as previously described (24) to quantify the relative activity of MMPs and TIMPs, respectively. Equal amounts of total protein from tissue homogenates were electrophoresed in acrylamide gels containing gelatin or casein substrate (zymography; Sigma, St. Louis, MO) or gelatin and recombinant human MMP-2 (reverse zymography; Oncogene Research Products, Cambridge, MA).…”
Section: Instrumentation and Treatment Protocolmentioning
confidence: 99%
“…In vivo studies have shown MMPs play a direct role in the development of allergic airway inflammation [114] and hyperresponsiveness [115][116][117]. Inflammatory cells, particularly neutrophils and alveolar macrophages, were thought to be the major source of increased proteinases in asthma and other inflammatory lung diseases [118,119], however several groups have demonstrated structural cells of the lung including the epithelium, also synthesize MMPs and their endogenous tissue inhibitors (TIMPs) [10,[120][121][122][123][124][125]. MMPs perform many biological functions, they are integral to connective tissue homeostasis and their activities are strictly coordinated during epithelial wound repair [124][125][126].…”
Section: Mmps In Asthma Glycosylation and Repairmentioning
confidence: 99%
“…IL-13 is also produced by a variety of non-hematopoietic cells including airway epithelial cells [119] and bronchial smooth muscle cells [114]. As a Th2 cytokine, IL-13 shares numerous overlapping characteristics with IL-4, where both cytokines promote B cell proliferation, IgE class switching and synthesis in B cells, and induce surface expression of antigens such as CD23 and major histocompatibility complex (MHC) class II [120]. These similarities between IL-13 and IL-4 function can be explained by the fact that the cytokines share a common receptor subunit, IL-4 receptor subunit (IL-4R ).…”
Section: Il-13 Functionmentioning
confidence: 99%